A finite viscoelastic constitutive model for filled rubber-like materials. (July 2015) - Hao, Dong; Li, Dongxu; Liao, Yihuan
Graphical abstract: Highlights: A constitutive model is proposed based on Lion and Hofer's models. The model is linearized in the neighborhood of predeformation. The model is applied to incompressible rubbery materials. Parameter identification and numerical aspects are shown. Experimental verification and numerical simulations are supplied. Abstract: Filled rubber-like materials show a significant dependence on predeformation, frequency and amplitude when they are loaded with static predeformations superimposed by harmonic deformations. In order to investigate this predeformation-, frequency- and amplitude-dependent material behavior, a recently developed constitutive model of finite viscoelasticity is proposed based on the models of Lion and Kardelky (2004) and Hofer and Lion (2009). The constitutive equations are geometrically linearized in the neighborhood of predeformation and then formulated for incompressible materials. Finally, the process of parameter identification and some numerical aspects are shown. Additionally, the experimental verification and some numerical simulations will also be supplied. The results show that our model cannot only be used for loading cases with small strains but also with large strains. It may have some meanings for practical engineering applications.